Kelekatan Antara Ibu dan Anak Usia Sekolah (Studi pada Ibu Sebagai Orang Tua Siswa Kelas 1 SDN Hanjuang Samijaya) - Santoso, Meilanny Budiarti; B, Megawati (Social Welfare Study Program, 2017)
Mother possesses a central role in the process of educating children. Mother spends more time with children at home than in the school. Thus, the attachment between the child and the mother becomes a benchmark as having required the ability to perform interaction within constructed social relations of school-aged children. This study was conducted using an explorative study that focused on the ‘eyecatching’ of information and issues that obtained in the process of this study. Interview, observation and documentation techniques are applied. The results show that the attachment between mother and child is built on the basis of the various skills that must be owned by school-aged children. This also means the role and function of the mother in educating school-aged children, expecially teaching process, that is caring, willingness to share, respect, politeness and responsibility. Providing good role models is the best way to instill values in children, thus becoming the foundation for good attachment building between mother and child. Keywords: attachment, mother, children, school-age children.